Dietary betaine supplementation improves meat quality of transported broilers through altering muscle anaerobic glycolysis and antioxidant capacity. (12th February 2020) - Chen, Rui; Wen, Chao; Gu, Yunfeng; Wang, Chao; Chen, Yueping; Zhuang, Su; Yanmin Zhou
Abstract: BACKGROUND: To investigate the effect of dietary betaine supplementation on growth performance, meat quality, muscle anaerobic glycolysis and antioxidant capacity of transported broilers, 1‐day‐old partridge‐shank‐broiler‐chickens ( n = 192) were randomly divided into three groups for a 50‐day feeding trial. The broilers in the control group were fed a basal diet, and experienced 0.75‐h transport before slaughter. The broilers in the other three groups were fed a basal diet supplemented with 0, 500 or 1000 mg kg −1 betaine, respectively, and experienced 3‐h transport before slaughter (T, T + BET500 or T + BET1000 groups). RESULTS: Dietary betaine supplementation increased ( P < 0.05) average daily gain of broilers, and feed conversion ratio was also improved ( P < 0.05) by 500 mg kg −1 betaine supplementation. Compared with the control group, 3‐h transport increased ( P < 0.05) live weight loss, serum corticosterone and cortisol concentrations, as well as muscle lactate and malondialdehyde (MDA) contents, and decreased ( P < 0.05) muscle pH24h, glycogen content and total superoxide dismutase activity. Compared with the T group, betaine supplementation decreased ( P < 0.05) serum corticosterone and cortisol concentrations and muscle MDA content, and increased ( P < 0.05) muscle a *24 h . In addition, 1000 mg kg −1 betaine supplementation further decreased ( P < 0.05) muscle drip loss, lactate content and lactate dehydrogenase activity, and increased ( P < 0.05) muscle glutathione content and glutathione peroxidase activity. CONCLUSION: Betaine supplementation not only improved growth performance of broilers, but also alleviated meat quality deterioration of transported broilers through altering muscle anaerobic glycolysis and antioxidant capacity. © 2020 Society of Chemical Industry